An empirical approach to river bed degradation - R K Calay; V K Sarda; R Dhiman (International Journal of Multiphysics, 2016)
Degradation in a homogeneous alluvial channel due to complete stoppageof sediment downstream of a high capacity reservoir has been studiedempirically. Based on dimensional analysis, a method has been establishedfor predicting transient bed profiles in degrading alluvial stream. In addition,prediction procedures for other degradation elements like maximumdegradation at any time at upstream section and degradation extent hasalso been evolved. The prediction procedures when tested against knowndata gave satisfactory results.